The Future of South African Research Universities - Stetar, Joseph (International Higher Education, 2015)
In recent decades a widely discussed aspect of higher education policy has been the relationship between universities at the center and those at the periphery—that is, between universities of the highly developed countries and those of developing countries. The debate has focused on the universities in developing countries and their disadvantage in the highly sophisticated, rapidly changing international or global knowledge network. The case of South Africa’s research universities illustrates the dilemmas.